Implementasi program pendidikan inklusif bagi siswa tunagrahita di Sekolah Dasar Kabupaten Garut Jawa Barat - Sam Amir, Yanti; Cahyani, Nurlita; Permana, Iqbal (Piramida Akademi, 2023)
Education and the administration of education must be managed well therefore increases the quality of students. One of the determining and supporting factors is the teacher. The role of teachers in elementary schools is really needed because elementary school students still need support from the environment in their learning process, especially students with special needs in inclusive elementary schools. This research aims to determine the implementation of the inclusive education program as well as school and teacher support activities for ABK students in inclusive education services and the obstacles they face. This research was conducted at three state elementary schools in the city of Garut. The subjects of this research were school principals, teachers and children with special needs. This research method uses qualitative methods through descriptive analysis techniques with case study studies using observation, interviews and document studies. The research results show that the mentally retarded students need special educational services which can develop their potential optimally. The curriculum and learning process need to be specifically designed to suit their needs. Inclusive education is a strategy in education where all students with special needs can receive the same educational services in regular schools. The inhibiting factor in this implementation are (1) the lack of teachers who have the competence to handle children with mentally retarded in elementary schools, (2) the lack of available facilities and infrastructure, and (3) the lack of coordination and communication that supports the implementation of inclusive schools.